Analysing the challenges of developing English for Specific Purpose (ESP) courses for Sino-Foreign cooperative educational programs - Huang, Zizhe; Mustakim, Siti Salina; Ghazali, Norliza (Jurnal Cakrawala Pendidikan, 2024)
With the increasing globalization and internationalization of higher education in China, Sino-foreign cooperative education programs are also flourishing. The English language and English language curricula and teaching are unavoidable topics in Sino-foreign cooperative education programs. The development of English for Specific Purposes (ESP) courses is directly related to the quality of talent cultivation in Sino-foreign cooperative educational programs. To promote the successful implementation of Sino-foreign cooperative education programs, this study takes the Sino-German Institute of Industrial Design (IDI) as an example to explore the challenges encountered in the development and practice of the English for Industrial Design (ESP) course under the Sino-foreign cooperative education program. This study aims to identify the current challenges of the ESP courses to enable students better to adapt to the foreign learning mode in advanced study and integrate into foreign cultures. This study utilized a qualitative research method of semi-structured interviews. In-depth interviews were conducted with one IDI director and two faculty members of IDI's ESP course. They were questioned about the problems and difficulties they encountered while conducting the ESP course. The study's results indicate challenges in the IDI's ESP courses concerning the background of course students, the selection of course materials, the quality of course teachers, and the teaching methods of the courses. The study analyzed the current state of ESP course development in Sino-foreign cooperative education programs, the challenges that significantly affect students' academic performance, and the successful teaching of IDI Sino-foreign cooperative education.